Anterior retroperitoneal approach in constructing thymokidney organs in swine for xenotransplantation - Gunes, M. Esad; Wolbrom, Daniel H.; Fujiwara, Sho; Qudus, Susan; Cadelina, Alexander; Nowak, Greg (Frontiers in Transplantation, 2024)
IntroductionThymokidneys (TK) have been constructed to transplant life-supporting kidney grafts containing donor thymic tissue to induce transplant tolerance. Historically, TKs were constructed by inserting pieces of thymus tissue under the kidney capsule using an intra-abdominal or posterior retroperitoneal (lateral/flank) approach. The intra-abdominal approach is technically easier but causes intra-abdominal adhesions and makes kidney procurement more challenging. The posterior retroperitoneal approach causes fewer complications, but thymus tissue implantation is technically demanding due to limited visibility and exposure of the kidney. We herein describe the anterior retroperitoneal approach that overcomes these challenges.Methods8-week-old GalTKO-swine (n = 2) were sedated, intubated, and draped. Cervical thymus lobes were isolated and excised. Via a small midline abdominal incision, the peritoneum was dissected bilaterally from the abdominal muscles, identifying both kidneys without entering the peritoneal cavity. Multiple thymus pieces were inserted under the kidney capsule. After 8 weeks, TKs were recovered for flow cytometric and histopathological analysis.ResultsIn all kidneys, we successfully constructed TKs with functional thymus tissue under the kidney capsule, verified by histopathology and flow cytometry. No surgical complications were observed, and no adhesions were observed intra-abdominally nor around the kidney, as the peritoneum covered the implanted tissue.ConclusionThe anterior retroperitoneal approach to constructing thymokidneys is easy to perform, offers excellent kidney exposure, allows a larger volume of thymus tissue to be implanted, and decreases the risk of intra-abdominal adhesions. Such constructed TKs are easy to procure with minimal risk of injury to the vascularized thymus as the prerenal peritoneum covers it.